2022
DOI: 10.3389/fphys.2022.850418
|View full text |Cite
|
Sign up to set email alerts
|

In Transgenic Erythropoietin Deficient Mice, an Increase in Respiratory Response to Hypercapnia Parallels Abnormal Distribution of CO2/H+-Activated Cells in the Medulla Oblongata

Abstract: Erythropoietin (Epo) and its receptor are expressed in central respiratory areas. We hypothesized that chronic Epo deficiency alters functioning of central respiratory areas and thus the respiratory adaptation to hypercapnia. The hypercapnic ventilatory response (HcVR) was evaluated by whole body plethysmography in wild type (WT) and Epo deficient (Epo-TAgh) adult male mice under 4%CO2. Epo-TAgh mice showed a larger HcVR than WT mice because of an increase in both respiratory frequency and tidal volume, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…As previously described ( Voituron et al, 2009 ; Niane et al, 2011 ; Samillan et al, 2013 ; Jeton et al, 2022 ), breathing variables were measured non-invasively in unanesthetized and unrestrained animals using whole-body flow barometric plethysmograph (Emka technologies, Paris, France). This method consists of measuring the pressure variations in a recording chamber during spontaneous ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described ( Voituron et al, 2009 ; Niane et al, 2011 ; Samillan et al, 2013 ; Jeton et al, 2022 ), breathing variables were measured non-invasively in unanesthetized and unrestrained animals using whole-body flow barometric plethysmograph (Emka technologies, Paris, France). This method consists of measuring the pressure variations in a recording chamber during spontaneous ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…The internal cellular sensors may include hypoxia and CO 2 ‐sensitive astrocytes and cardiorespiratory neurons (Patterson et al., 2021 ), although this has recently been questioned (Li et al., 2023 ). Classically, the CNS was believed to lack hypoxia sensors, but work in rodents (Herlenius, 2011 ; Hofstetter & Herlenius, 2005 ; Hofstetter et al., 2007 ; Sheikhbahaei et al., 2018 ) has shown that (1), mitochondria within astrocytes (for example, within the preBötC) are susceptible to local hypoxia (Sheikhbahaei et al., 2018 ); (2), astrocytes at multiple sites, including in the NTS, MRN and RTN/pFRG, are sensitive to the brain's parenchymal levels of metabolites (pH, glucose, O 2 and CO 2 ), to prostaglandin E2 (PGE2), and to certain hormones and neurotransmitters (Forsberg & Herlenius, 2019 ; Funk, 2010 ; Marina et al., 2018 ); and (3), the cardiorespiratory neurons in the NTS, MRN and RTN act as central pH sensors through a complex mechanism including Ca 2+ channels and connexin‐mediated ATP release (Forsberg et al., 2016 ; Funk, 2010 ; Gourine et al., 2010 ; Jeton et al., 2022 ). In the two putative chemoreceptive sites, the MRN and RTN, elevation of CO 2 , independent of pH change, mediates chemosensation following a connexin‐mediated release of ATP (Funk, 2010 ), and hypercapnia has been shown to induce connexin‐mediated ATP and PGE2 release from pFRG/RTN astrocytes, which in turn increases the activity of pFRG/RTN neurons and subsequent inspiratory frequency (Forsberg et al., 2016 ; Forsberg et al., 2017 ; Gourine et al., 2010 ; Huxtable et al., 2010 ).…”
Section: Brainstem Response To Hypoxiamentioning
confidence: 99%